Teleguided photocoagulation treatments across continents with a remotely programmed laser for retinal diseases - Andrea Cusumano; Robin Ross; Benedetto Falsini; Marco Lombardo (Therapeutic Advances in Ophthalmology)
Diabetic retinopathy and retinal vein occlusion represent two prevalent vision-threatening retinal diseases. Retinal laser therapy still plays an important role in treating these conditions, but its successful administration often requires referral to specialized centers and retina experts. It is, therefore, essential to develop a new treatment methodology that enables patients to benefit from the expertise of specialists from reference centers. For this purpose, we investigated the feasibility of teleguided photocoagulation conducted across continents to determine if different ophthalmologists can consensually devise and safely execute treatment plans remotely. Two patients from Italy (Europe) with diabetic retinopathy and one from Arizona (USA) with central retinal vein occlusion underwent retinal photocoagulation using Navilas ® 577s with remote teleguidance from the corresponding continental counterpart. The process included remote planning and execution, supported by an audio connection for real-time communication. Teletreatment success criteria included treatment plan completion, patient tolerance, remote connection stability, and technical quality. All treatments have been successfully performed with accurate spot application and no technical issues. Follow-ups at three weeks confirmed positive outcomes for each patient. Remote teleguided retinal photocoagulation appears feasible, offering a promising tool for global collaborations in retina care and potential benefits to regions with limited access to expert supervision.